2017
DOI: 10.1111/cid.12576
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of quality of life and satisfaction between implant bar overdentures and conventional complete dentures: A 23 years retrospective study

Abstract: Implant overdentures on cobalt chrome and gold bars offer an excellent long-term solution for edentulism compared with conventional denture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
0
18
0
2
Order By: Relevance
“…Two implant‐retained mandibular overdentures provide a simple and cost‐effective alternative that should be implemented more frequently in low‐ and middle‐income countries . Since the publication of the McGill and York Consensus, implant‐retained mandibular overdentures are considered the minimum protocol for rehabilitation of edentulous individuals, mainly because of the increased retention and stability of the mandibular prosthesis, which in turn improves retentive forces and benefits masticatory function . Although the McGill Consensus Statement states that mandibular overdentures retained by 2 implants should be widely recommended as the minimal protocol for rehabilitation of totally edentulous individuals, a systematic review by Fitzpatrick concluded that there is still no strong evidence to support only a single standard of care in edentulous jaws.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two implant‐retained mandibular overdentures provide a simple and cost‐effective alternative that should be implemented more frequently in low‐ and middle‐income countries . Since the publication of the McGill and York Consensus, implant‐retained mandibular overdentures are considered the minimum protocol for rehabilitation of edentulous individuals, mainly because of the increased retention and stability of the mandibular prosthesis, which in turn improves retentive forces and benefits masticatory function . Although the McGill Consensus Statement states that mandibular overdentures retained by 2 implants should be widely recommended as the minimal protocol for rehabilitation of totally edentulous individuals, a systematic review by Fitzpatrick concluded that there is still no strong evidence to support only a single standard of care in edentulous jaws.…”
mentioning
confidence: 99%
“…12 Since the publication of the McGill and York Consensus, implant-retained mandibular overdentures are considered the minimum protocol for rehabilitation of edentulous individuals, 13 mainly because of the increased retention and stability of the mandibular prosthesis, which in turn improves retentive forces and benefits masticatory function. [14][15][16][17][18] Although the McGill Consensus Statement states that mandibular overdentures retained by 2 implants should be widely recommended as the minimal protocol for rehabilitation of totally edentulous individuals, a systematic review by Fitzpatrick concluded that there is still no strong evidence to support only a single standard of care in edentulous jaws. The outcomes of this study suggest that patient choice has a greater impact on treatment success than the dentist's treatment preferences and highlight the importance of informing edentulous patients about the surgical risks to enable them to make an informed decision.…”
mentioning
confidence: 99%
“…All these factors are responsible for the low oral healthrelated quality of life perceived by the patients wearing removable dentures [1]. This explains why a better quality of life can be achieved with implant-retained prosthesis compared to conventional dentures in terms of physical pain and disability, psychological discomfort and disability, and functional limitations [2]. It must be noted that edentulism can lead to a significant functional impairment together with unfavourable aesthetic and psychological changes in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that overdentures can provide better retention and stability and are more easily accepted by patients compared with conventional dentures [3]. Also, overdentures can easily provide optimal lip and soft tissue support [4].…”
Section: Introductionmentioning
confidence: 99%